Pressure and Temperature Dependence of the Raman Peak Intensity Ratio of Asymmetric Stretching Vibration (ν3) and Asymmetric Bending Overtone (2ν2) of Methane. Issue 5 (May 2014) - Wang, Menghan; Lu, Wanjun; Li, Lanlan; Qiao, Shaohua
Raman peaks of the asymmetric stretching vibration (ν3 ) and the asymmetric bending overtone (2ν2 ) of methane were studied at elevated pressures and temperatures, from 3 to 51 MPa and from 298.15 to 473.15 K. The peak intensity ratios of ν3 and 2ν2 were calculated, and the relationship among peak intensity ratio, temperature, and pressure/density were derived using equations. Such relationships allow geologists to determine the pressure and density of methane fluid inclusions using Raman spectroscopic measurements of the peak intensity ratios of ν3 and 2ν2 .